Amber House - Moore, Kelly (Kelly Sheelagh); Reed, Tucker; Reed, Larkin (New York : Arthur A. Levine Books, 2012)
After her grandmother's death Sarah Parsons delights in exploring her family's Maryland estate with new friend Jackson, but soon she is having visions of her ancestors, one of whom may be a threat to Sarah's autistic brother, Sam.
Keywords: Psychics -- Fiction; Houses -- Fiction; Visions -- Fiction; Siblings -- Fiction; Family life -- Fiction -- Maryland; Maryland -- Fiction; Mystery fiction